2019
DOI: 10.1108/sjme-12-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

From Instagram overuse to instastress and emotional fatigue: the mediation of addiction

Abstract: Purpose Today’s society interest in mobile photography drives consumers’ and brands’ growing usage of Instagram. This paper aims to address the consequences of excessive use of Instagram on the negative feeling of losing information when not connected and the emotional fatigue resulting from an overcharge with new information. The mediating role of addiction between Instagram overuse and the two outcomes is also analyzed. Design/methodology/approach Data from 342 active Instagram users were used to test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 75 publications
(92 reference statements)
4
18
0
4
Order By: Relevance
“…Its measures were often used to explore the individuals’ intentions to watch specific programs on television (Stafford et al , 2004; Harwood, 1999) or to investigate their engagement with digital media, including internet technologies (Kaur et al , 2020; Shao, 2009; Flavián and Gurrea, 2008) and social media (Dhir et al , 2017a; Mäntymäki and Riemer, 2014; Smock et al , 2011). For example, Sanz-Blas et al (2019), as well as Mäntymäki and Islam (2016) have used UGT to shed light on the adverse effects of social media on teenagers. Other researchers relied on this model to examine the individuals’ gratifications from mobile instant messaging (Kaur et al , 2020), food delivery apps (Ray et al , 2019) and digital photo sharing with other social media subscribers (Malik et al , 2016), among other contemporary topics.…”
Section: The Technology Acceptance Of Online Streaming Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its measures were often used to explore the individuals’ intentions to watch specific programs on television (Stafford et al , 2004; Harwood, 1999) or to investigate their engagement with digital media, including internet technologies (Kaur et al , 2020; Shao, 2009; Flavián and Gurrea, 2008) and social media (Dhir et al , 2017a; Mäntymäki and Riemer, 2014; Smock et al , 2011). For example, Sanz-Blas et al (2019), as well as Mäntymäki and Islam (2016) have used UGT to shed light on the adverse effects of social media on teenagers. Other researchers relied on this model to examine the individuals’ gratifications from mobile instant messaging (Kaur et al , 2020), food delivery apps (Ray et al , 2019) and digital photo sharing with other social media subscribers (Malik et al , 2016), among other contemporary topics.…”
Section: The Technology Acceptance Of Online Streaming Servicesmentioning
confidence: 99%
“…Other research investigated the individuals’ gratifications from social networking services (SNS) including Facebook, Instagram, Twitter and Linkedin, as well as blogs and review websites (Bevan-Dye, 2020; Capriotti et al , 2020; Belanche et al , 2019; Sanz-Blas et al , 2019; Leung, 2013; Park et al , 2009). Many authors have used UGT to explore the gratifications of social media subscribers as more individuals are becoming devoted, engaged and highly motivated to upload content in specific SNS services (Rios Marques et al , 2020; Malik et al , 2016).…”
Section: The Technology Acceptance Of Online Streaming Servicesmentioning
confidence: 99%
“…Over the last two decades, the use of Social Networking Sites, such as Facebook, Twitter and Instagram, has evoked rapidly. Research has shown that social media use may improve human interaction, psychological wellbeing and the learning process (Baumer, 2013;Garrett and Cutting, 2012;Baumöl et al, 2016;Schultz, 2016;Hutter et al, 2013). Nevertheless, a growing body of evidence has shown that a negative side of social media also exists (Mäntymäki, and Islam, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Casaló et al (2017) reported that perceived originality positively affected intention of Instagram users by increasing perceived hedonism. Sanz-Blas et al (2019) demonstrated that overuse of Instagram led to greater stress and emotional fatigue.…”
Section: Literature On Instagrammentioning
confidence: 99%